Role of cannabinoids in the regulation of bone remodeling - Idris, Aymen I.; Ralston, Stuart H. (Frontiers in Endocrinology, 2012)
The endocannabinoid system plays a key role in regulating a variety of physiological processes such as appetite control and energy balance, pain perception, and immune responses. Recent studies have implicated the endocannabinoid system in the regulation of bone cell activity and bone remodelling. These studies showed that endogenous cannabinoid ligands, cannabinoid receptors and the enzymes responsible for ligand synthesis and breakdown all play important roles in bone mass and in the regulation of bone disease. These findings suggest that the endocannabinoid pathway could be of value as a therapeutic target for the prevention and treatment of bone diseases. Here, we review the role of the skeletal endocannabinoid system in the regulation of bone remodelling in health and disease.